2014
DOI: 10.1002/stem.1783
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Murine Periosteal Progenitor Cells with Fibroblast Growth Factor 2 Reveals an Intrinsic Endochondral Ossification Program Mediated by Bone Morphogenetic Protein 2

Abstract: The preservation of the bone-forming potential of skeletal progenitor cells during their ex vivo expansion remains one of the major challenges for cell-based bone regeneration strategies. We report that expansion of murine periosteal cells in the presence of FGF2, a signal present during the early stages of fracture healing, is necessary and sufficient to maintain their ability to organize in vivo into a cartilage template which gives rise to mature bone. Implantation of FGF2-primed cells in a large bone defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 57 publications
3
88
0
Order By: Relevance
“…However, it is probable that when used in reduced dose in combination with small chemical molecules (like NMP) it may stimulate the bone forming potential of the implanted cells, but the clinical evidence is lacking. Alternatively, the use of growth factors can be restricted to the pre-implantation cell expansion phase in order to enhance the regenerative potency of the implanted MSCs and thereby prevent possible side effects caused by in vivo application of growth factors [63]. …”
Section: Bone Regeneration: Challengesmentioning
confidence: 99%
“…However, it is probable that when used in reduced dose in combination with small chemical molecules (like NMP) it may stimulate the bone forming potential of the implanted cells, but the clinical evidence is lacking. Alternatively, the use of growth factors can be restricted to the pre-implantation cell expansion phase in order to enhance the regenerative potency of the implanted MSCs and thereby prevent possible side effects caused by in vivo application of growth factors [63]. …”
Section: Bone Regeneration: Challengesmentioning
confidence: 99%
“…An initial damage-control operation is recommended to remove all contaminating materials and to provide temporary bone stabilization. 2,16 All devitalized skin, muscle, periosteum, and sequestrated bone tissue should be excised during debridement procedures to gain sufficient control of …”
Section: Discussionmentioning
confidence: 99%
“…2 Often, the damaged periosteum cannot be repaired directly during treatment because of the significant stripping injuries and tissue losses that occur in association with open fractures. 3 The management of severe open fractures poses several challenges for surgeons because open fractures are associated with numerous problems, including infections, tissue defects, and nonunions.…”
mentioning
confidence: 99%
“…We found that RA-sera did inhibit matrix mineralization in ATDC5 but not in HPDC micromasses. This difference might be explained by differences in the cell populations we used, that is, the ATDC5 murine cell line represents a homogeneous cell population, while the periost-derived cells represent a more heterogeneous population, containing fibroblasts, skeletal progenitors, and endothelial progenitors (40,41). This difference might also be the result of differences in the degree of inflammation of the patients from whom the active RA-sera were obtained.…”
Section: Discussionmentioning
confidence: 99%